Nonsyndromic Oral Clefts and COVID-19 Crisis: Some Considerations on the Delay in Clinical Management of Patients - Hercílio Martelli-Júnior; Renato Assis Machado; Daniella R. Barbosa Martelli; Ricardo Della Coletta; Mário Sérgio Oliveira Swerts (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Dear Editor,